2006
DOI: 10.1101/gad.397006
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of PER2 phosphorylation: molecular basis for the human familial advanced sleep phase syndrome (FASPS)

Abstract: PERIOD (PER) proteins are central components within the mammalian circadian oscillator, and are believed to form a negative feedback complex that inhibits their own transcription at a particular circadian phase. Phosphorylation of PER proteins regulates their stability as well as their subcellular localization. In a systematic screen, we have identified 21 phosphorylated residues of mPER2 including Ser 659, which is mutated in patients suffering from familial advanced sleep phase syndrome (FASPS). When express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
406
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(422 citation statements)
references
References 51 publications
16
406
0
Order By: Relevance
“…Interestingly, the oscillation dynamics of PER2-FASPS expressing cells is very similar to the behavior of FASPS patients: an early phase of entrainment and a short free-running period ( Fig. 1) (Vanselow et al 2006).…”
Section: Mapping Of Phosphorylation Sites In Clock Proteinsmentioning
confidence: 58%
See 2 more Smart Citations
“…Interestingly, the oscillation dynamics of PER2-FASPS expressing cells is very similar to the behavior of FASPS patients: an early phase of entrainment and a short free-running period ( Fig. 1) (Vanselow et al 2006).…”
Section: Mapping Of Phosphorylation Sites In Clock Proteinsmentioning
confidence: 58%
“…The mass spectrometric approach mentioned above led to the identification of 21 (of 275 theoretically possible) endogenous phosphorylation sites in mPER2 (exclusively serine and threonine residues). Interestingly, we found the serine residue phosphorylated, which is mutated in FASPS (Vanselow et al 2006). This is the first direct evidence that the FASPS site is indeed a target for phosphorylation in living cells.…”
Section: Mapping Of Phosphorylation Sites In Clock Proteinsmentioning
confidence: 62%
See 1 more Smart Citation
“…It involves interlocked feedback loops (Glossop et al 1999;Lee et al 2000;Ripperger & Schibler 2001). Moreover, experiments showed that multiple phosphorylations of the PER protein have differential effects on the protein degradation and translocation in the nucleus (Vanselow et al 2006;Xu et al 2007). Finally, the Michaelis-Menten term used in this study assumes an enzymatic process but other sources of nonlinearity in the degradation kinetics may also be present, such as the cooperative dimerization of proteins, which was shown to affect the dynamics of genetic circuits (Buchler et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even individuals that are genetically predisposed towards "eveningness" (a preference for the evening) versus "morningness" (a preference for the morning) are more likely to develop depression (Drennan et al, 1991;Chelminski et al, 1999). Genetic variations in the circadian genes have been found to associate with these sleep disorders and diurnal preference measures including an association between certain variants of Per2, and CK1δ with FASPS; Per3, CLOCK, and CK1ε with DSPS; and Per1, Per2, Per3 and CLOCK with diurnal preference (Katzenberg et al, 1998;Iwase et al, 2002;Archer et al, 2003;Johansson et al, 2003;Takano et al, 2004;Carpen et al, 2005;Mishima et al, 2005;Xu et al, 2005;Carpen et al, 2006;Vanselow et al, 2006). This suggests a connection between proper mood regulation and a normal functioning circadian clock.…”
Section: A Generally Disrupted Clockmentioning
confidence: 99%